VERSES OF THE QUR'AN AND THE NYADRAN RITUAL : ETHNOGRAPHIC STUDY PHENOMENOLOGY IN JAVANESE MUSLIM COMMUNITY - Samsul Ariyadi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Study This aiming For analyze integration Al-Qur'an verses in the Nyadran ritual through approach qualitative descriptive with use analysis thematic . The study was conducted in the Muslim community of Central Java with involving 20 religious figures and Nyadran ritual practitioners . Data obtained through Focus Group Discussion (FGD) and documentation direct on implementation of rituals, as well as analyzed use approach phenomenology of religion and ethnography . This study limited to aspects prayer and dhikr in the Nyadran ritual , in order to enrich understanding about the concept of 'living Quran' in culture local . Research results disclose that integration the verses of the Qur'an play a role important in formation meaning religious and social in the middle community , where prayer and remembrance exist in the nyadran ritual reflect dynamics living and adaptive faith​ to context Javanese culture . Data validity is guaranteed through member checking and peer review , as well as supported by studies literature from 25 articles Scopus indexed for five years last . Implications study This No only give contribution academic to studies Islam and culture local , but also open opportunity development more ritual methods inclusive and contextual .